Facing the globalisation challenge in the realm of English language teaching - Sifakis, N.; A.-M. Sougari (Language and Education, 2003)
The paper addresses the commonly acknowledged challenge of globalisation with respect to the area of English language teaching and, more particularly, teaching English to speakers of foreign languages. It is argued that some of the primary issues involved concern the increasing role of technology and communication in modern societies and the looming conflict between local communities and the decision-making bodies. It is further suggested that the global English language teaching (ELT) community has already gone a long way towards researching and, in certain cases, resolving such conflicts and has much insightful material to offer. The paper incorporates a discussion of the notion of English as an international language and the question of 'ownership' of such a language. The roles and defining characteristics of the native and non-native speaker of English are then considered and the various occasions when communication and learning take place are briefly reviewed, with frequent reference to the authors' own teaching situation, i.e. English language teaching in Greece. The paper culminates with an appreciation of the pedagogical, ethical and methodological considerations that are suggested as a means of sensitising TESOL teacher education vis à vis the global status of English (also with the Greek context in mind).